PSYCHIATRIC INPATIENT INSTALLATION BUSINESS STRATEGY AT THE PSYCHIATRIC HOSPITAL DR. H. MARZOEKI MAHDI - Renea Shinta Aminda; Asri Masitha Arsyati; Risca Irawan (Manajemen Bisnis, 2021)
The problem that is the object of research is the number of people experiencing mental health disorders due to the Covid 19 pandemic becomes a new source of stress for the global community today. This research is qualitative with an analytical descriptive problem analysis approach using strategy formulation tools in the form of IFE matrix, EFE matrix, TOWS matrix, IE matrix.). Based on the results of the study. Total EFE Matrix score of 2.90. Ife Matrix total score of 2.41. With the merger of TOWS Matrix and IE Matrix, the right strategy for Dr. H. Marzoeki Mahdi's Mental Hospital is product development. With QSPM  the strategy is to develop services that are adaptive to pandemic conditions but still refer to the strategic and business plans that have been established, strengthening the competence of nurses in Psychiatric Hospitalization Installations, utilization of IT in the service process, the preparation of guidelines for psychiatric inpatient installation infrastructure facilities, increasing partnership efforts across programs and across sectors.